Earth-based Render of Tabique Walls – An Experimental Work Contribution. Issue 2 (17th February 2017) - Pinto, Jorge; Cunha, Sandra; Soares, Nuno; Soares, Edgar; Cunha, Vítor M. C. F.; Ferreira, Débora; Sá, Ana Briga
ABSTRACT: A research work focused on studying earth render for tabique application purposes is presented. Initially, a brief description of the tabique building technique is provided. The relevance of the application of this traditional building technique is also highlighted. Different compositions of earth render are experimentally analyzed and the respective performance is evaluated. Flexural and compressive strengths, workability, drying shrinkage cracking, and water resistance are the material properties assessed. A simple earth render is selected as being adequate for tabique building applications and it is applied on the manufacturing of a tabique wall sample. This wall sample is monitored in terms of thermal insulation ability and its thermal transmission coefficient is estimated. Taking into account that there is still a lack of published technical information related to this topic, this article may contribute to solve this limitation and to give some guidance in future repairing processes of tabique construction. The technological benefit of adding lime or cement with earth is researched. Real tabique timber structure samples are applied in order to validate the obtained experimental results.